The Moderating Effect of Bank Size on the Relationship Between Risk and Profitability in ASEAN Banking During the COVID-19 Pandemic - Herlina, Herlina; Wilujeng, Fuji Rahayu (Journal of Indonesian Economic Research, 2025)
This study examines the moderating role of bank size in the relationship between risk and profitability in ASEAN banking during the COVID-19 pandemic. The sample consists of 24 banks in ASEAN countries, with annual data from 2019 to 2021, resulting in a total of 96 panel data observations. The findings indicate that bank size plays a crucial role in enhancing profitability, as larger banks tend to have higher profitability due to better risk management capabilities and greater access to financial resources. Meanwhile, risk does not have a significant direct impact on profitability, suggesting that banking policies and government interventions during the pandemic helped mitigate financial pressures. However, the interaction between risk and bank size reveals a negative moderating effect, indicating that risk has a more significant adverse impact on smaller banks compared to larger ones. These findings emphasize the importance of banking resilience and financial stability strategies in ensuring sustainable growth in the post-pandemic era. Therefore, regulators and policymakers should pay greater attention to supporting smaller banks to enhance their ability to withstand economic shocks.